Photodegradation of Basic Brown 16 Dye from Aqueous Solution Using Bio-Synthesized ZnO Nanoparticles in Bitter Gourd Peels Extract: A Review - FRANCIS, FEIDEL MICANG; Ts. Dr. ADEL ALI SAEED ABDUH ALGHEETH, (Recent Trends in Civil Engineering and Built Environment, 2022)
Most metal-based nanoparticle synthesis methods are known to generate hazardous by-products. Green synthesis, however, is more eco-friendly in producing metal nanoparticles. In this research, bitter gourd peel extract was synthesised as a method to detect the breakdown of Basic Brown 16. This research is designed to help water treatment organisations address the need for coloured wastewater treatment. Liquid waste including hair dye leftovers and other industrial waste is a source of environmental pollution. Basic Brown 16 dye is the major topic of this study. The dye itself, as is mentioned above, is Brown 16. ZnO NPs photocatalytic efficacy will be evaluated based on decolorization of Basic brown 16. To be pursued is the effectiveness of produced ZnO NPs in bitter gourd peels extract in Basic Brown 16 dye wastewater removal. FESEM and EDX (EDX). Efficiency of photocatalysis of BB16 with ZnO NPs will be improved using Response Surface Methodology (RSM), while the removal mechanism will be studied via SEM-EDX, AFM, and FTIR. This project aims to come up with a better method for extracting Basic Brown 16 dye from wastewater. By using crop residues, ZnO synthesis may reduce the massive amounts of trash produced. ZnO nanoparticles will offer efficient treatment technique for dye wastewater.